2023
DOI: 10.3390/bs13090739
|View full text |Cite
|
Sign up to set email alerts
|

“Fill the World with Love”: Songs with Prosocial Lyrics Enhance Online Charitable Donations among Chinese Adults

Mei Hong,
Dapeng Liang,
Teng Lu

Abstract: Research has shown that songs with prosocial lyrics can enhance individual prosociality. Building on the general learning model (GLM), this study demonstrated, through real-world charitable organizations, how songs with prosocial lyrics influence helping behavior that uses time as a currency. In Study 1, participants were randomly assigned to conditions of prosocial songs, prosocial lyrics, or neutral songs, and they were instructed to complete an online charity task. The results indicated that compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…These findings add to the current knowledge on this topic and previous findings that showed that live music can stimulate prosocial emotions such as empathy and compassion (Gilbert et al, 2023;Hong et al, 2023;McDonald et al, 2022), enhance social connection between healthcare staff and patients (Daykin et al, 2018;Dingle et al, 2021) and in nurse-patient interactions (van der Wal-Huisman et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…These findings add to the current knowledge on this topic and previous findings that showed that live music can stimulate prosocial emotions such as empathy and compassion (Gilbert et al, 2023;Hong et al, 2023;McDonald et al, 2022), enhance social connection between healthcare staff and patients (Daykin et al, 2018;Dingle et al, 2021) and in nurse-patient interactions (van der Wal-Huisman et al, 2020).…”
Section: Discussionsupporting
confidence: 76%
“…Such positive initiatives by peers can contribute to positive emotions like adolescents' social tolerance and self-confidence (Repper and Carter, 2011), suggesting that OB holds the potential to assist adolescents in navigating challenges encountered in their personal growth. However, the current body of research on adolescent online prosocial behavior remains limited, with most studies concentrating on online prosocial behavior in adult samples (Hong et al, 2023). Consequently, this paper deems it imperative to specifically explore the driving factors and behavioral mechanisms underlying adolescent online prosocial behavior.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The WEBT differs from the PEBT as it runs online, and participants can choose to spend time completing monotonous tasks (counting numbers on a page) in return for money being donated to environmental charities. The WEBT therefore is similar in premise to research on more general prosocial behavior that uses the Free Rice game, where participants spend time completing tasks in exchange for rice being donated to the World Food Programme (Farmer & Farrelly, 2023;Farrelly & Bennett, 2018;Hong et al, 2023). This range of performance-based experimental protocols have been effectively used to measure pro-environmental behavior, however each have practical limitations that may prohibit more widespread and diverse use.…”
Section: Introductionmentioning
confidence: 99%